(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article examines current and future startup projects as well as their expected economic and social outcomes. In recent years, startups have become an essential driver of innovation, technological advancement, and entrepreneurial activity worldwide. They not only create new jobs but also promote competitiveness, attract investment, and contribute to sustainable development.